CHALLENGES IN ACHIEVING LEXICAL AND SEMANTIC EQUIVALENCE IN THE TRANSLATION OF ENGLISH ENVIRONMENTAL TERMS INTO RUSSIAN - Tukhtasinova N.I. (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
Currently, environmental pollution and the search for effective solutions represent one of the most important focuses in modern scientific research. Successfully addressing these environmental challenges requires access to precise and specialized information, much of which is available primarily in English. This study examines the primary difficulties encountered when translating English environmental terminology into Russian. It explores the fields where these terms are used and identifies criteria that guarantee the accuracy and adequacy of their translation.